APPLICATION SETTINGS parking lot and retribution IN CARS WITH CARDS storey building electrical - Eriek Orlando (JAKSTIK Journal, 2003)
Number of companies and shopping centers that have employees or visitors in a very largeamount of parking needed large enough to put their fleet. Prototype system for managingparking lot parking lot has been realized, the system is using Borland Delphi 5 application asan application fee and application programming BASCOM as to set the microcontrollerAT89S52 as controller hardware. With this system, can help the building managers inmanaging parkirannya to be more organized and make profit, karenakan not require too muchstaff and the accuracy of counting the cost of parking. In addition, users also get theconvenience of parking their vehicles in place and not feel disadvantaged will be no parkingfees in accordance with the established.